Analyzing thyroid dysfunction in the climacteric - Subrat Panda; Ananya Das (Wolters Kluwer Medknow Publications, 2018)
Introduction: Perimenopause and menopause is an integral part of every woman's life constituting about 30% of the Indian female population. Hypothyroidism is a condition that can mimic menopausal symptoms very often. Therefore, routine screening of thyroid function in the climacteric and menopausal period to determine subclinical thyroid disease can be recommended. Materials and Methods: With this background, we conducted a prospective study in our institute, North Eastern Indira Gandhi Regional Institute of Health and Medical Sciences, to evaluate the abnormal thyroid function tests in perimenopausal and postmenopausal women aged 40-80 years. Results and Observations: Subclinical hypothyroidism status increases from the age group of 40-70 years and hypothyroidism increases in slow frequency from 40 to 70 years after that there is plateauing. Interestingly, the frequency of hyperthyroidism remains same in all the age groups. Conclusion: Looking at the increased risks of thyroid disorders with age, screening of thyroid disorders can be started at the age of 40 years with estimation of serum levels of TSH. This gives us the opportunity to treat both subclinical and clinical hypothyroidism and hyperthyroidism women.